Antoni van Leeuwenhoek: defining proportion in the microscopic realm during the 17th century - Davis, Ian M. (2022)
This article examines comparisons Antoni van Leeuwenhoek made between everyday objects, such as grains of sand, millet seeds, and hairs, and the structures and objects he observed through his single-lens microscopes. These comparisons, their possible origins in commerce, and the variety of Leeuwenhoek's observations have not been appreciated widely for their elegance. His measurement of the microscopic world might have grown out of his time as an apprentice to William Davidson, an international cloth merchant in Amsterdam, Leeuwenhoek's surveying licensure, drapery business, and other commercial experiences in Delft. Leeuwenhoek initiated the use of comparisons in his 28 April 1673 letter to the Royal Society, his first letter describing his observations. He compared animalcules, blood cells, fat globules, veins and arteries, insect, plant, and mineral structures to a range of conventional, although tiny objects such as fine and coarse grains of sand, millet grains, human hairs, and other items. In many of his comparisons, he arrived at size estimates for the objects that are very close to the sizes found using current instruments and techniques. Examples of Leeuwenhoek's comparisons will be provided.